2017
DOI: 10.1016/j.taap.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to toxicologic lung responses among inbred mouse strains following exposure to carbon nanotubes and profiling of underlying gene networks

Abstract: The risk of human exposure to fiber nanoparticles has risen in recent years due to increases in the manufacture and utilization of carbon nanotubes (CNTs). CNTs are present as airborne particulates in occupational settings and their hazard potential has been demonstrated in experimental lung exposure studies using inbred mouse strains. However, it is not known whether different inbred strains differ in lung responses to CNTs by virtue of their genetics. In this work, common inbred strains (BALB/c, C57Bl/6, DBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The AQP3-mediated uptake of H 2 O 2 , is critical for chemokine-dependent T cell migration ( Hara-Chikuma et al, 2012 ). This is in concordance with our published and current findings which showed that inhalation exposure to CNT nanoparticles induces inflammation ( Frank et al, 2015 ; Frank et al, 2016 ; Frank et al, 2017 ) and upregulates AQP3 (current study) in exposed mouse lungs. This is also corroborated by the lung histology data which showed marked inflammatory changes in the CNT-exposed lungs in terms of infiltrated immune cells and granulomatous reactions.…”
Section: Discussionsupporting
confidence: 94%
“…The AQP3-mediated uptake of H 2 O 2 , is critical for chemokine-dependent T cell migration ( Hara-Chikuma et al, 2012 ). This is in concordance with our published and current findings which showed that inhalation exposure to CNT nanoparticles induces inflammation ( Frank et al, 2015 ; Frank et al, 2016 ; Frank et al, 2017 ) and upregulates AQP3 (current study) in exposed mouse lungs. This is also corroborated by the lung histology data which showed marked inflammatory changes in the CNT-exposed lungs in terms of infiltrated immune cells and granulomatous reactions.…”
Section: Discussionsupporting
confidence: 94%
“…Versatility of this approach was demonstrated by the discrimination of three mouse strains, outbred mouse Slc:ddY, inflammatory inbred mouse DBA/2Crslc 54 , 55 , and MRL- lpr / lpr mice 56 , 57 known as a disease model mouse of SLE syndrome 58 , based on the differences in the lung N -glycosylation pattern according to the above examination protocol for the machine learning algorisms. Although the purpose of our study by means of these disease model mouse strains is to discover novel glycan-related biomarkers in various lung inflammation (idiopathic pulmonary fibrosis), infection, cancer, and autoimmune disease ( https://www8.cao.go.jp/cstp/panhu/prism2021_e/2021.html ), it was thought that this preliminary assessment may implicate general potentials, merits, and feasibility of our approach based on the mouse tissue glycome atlas in a variety of studies using designated model mice.…”
Section: Resultsmentioning
confidence: 99%
“…However, the majority of such studies, including our own, on microbiome-toxicant pathology interactions have focused on the gut microbiome [12][13][14][15]26] and little is known about the role of the oral and respiratory microbiomes. While cigarette smoking has been shown to modulate human oral and lung microbiomes [22][23][24] such evidence is lacking for other toxic particulate types, particularly for carbon nanotubes, the high-volume engineered nanoparticles that are known to cause lung damage and pathological conditions [4][5][6]. In this context, our most recent studies have shown that respiratory exposure to CNTs can remotely induce dysbiosis in gut microbiota [7].…”
Section: Discussionmentioning
confidence: 99%
“…The past decade has seen several epidemiological and animal studies highlighting the toxicity and respiratory effects of CNTs [2]. Published rodent model studies including our own indicate their potential to induce lung inflammatory episodes causing acute response and chronic toxicologic immunopathology characterized by inflammation, hyperplasia, and granulomatous lesions [3][4][5][6]. Our sub-chronic mouse model studies have shown that hyperplasia in response to inhaled CNTs preferentially involves the proliferation of type 2 pneumocytes (T2Ps), also known as alveolar type II epithelial cells lining the alveoli, conceivably to heal the injury and maintain epithelial integrity [5].…”
Section: Introductionmentioning
confidence: 99%